DEVELOPMENT OF AN AIR HEATING AND HUMIDIFYING SYSTEM FOR MECHANICAL VENTILATION OF INTENSIVE CARE UNIT PATIENTS - Ferreira, E. L.; Vargas, J. V. C.; Campos, M. C.; Dias, F. G.; Ordonez, J. C.; Brioschi, M. L.; Botelho, E. F. (Revista de Engenharia Térmica, 2009)
The mechanical ventilators, also named artificial ventilators, are devices used in Intensive Care Units (ICU) for clinically critical patients. The equipment provides artificial breathing for the patient, creating favorable conditions for the patient recovery. It works as a system that is connected to the electric grid and two other networks, one supplies compressed air and the other supplies pure oxygen. Inside the equipment the gases are mixed, and then warmed up and humidified to be finally delivered to the patient. The existing system for treatment of the mixture is not effective, since it delivers the breathing air to the patient out of the normal physiology recommended range, i.e., temperature ~32-34°C and relative humidity ~80-95%. The objective of this work was to develop a new air heating and humidifying system for mechanical ventilation. First, it was built an air feeding system, composed by a compressor and an electronically controlled valve to simulate an actual mechanical ventilation system in the laboratory. A device for conditioning the air (temperature and humidity) was conceived and built for treating the air feeding system output air. The results of the laboratory measurements show that the developed equipment was capable of making the breathing air to reach the recommended ranges by the normal physiology.